Relationship between decision-making and performance in game actions in volleyball - Conejero Suarez, M.; Claver, F.; Fernández-Echeverria, C.; Moreno, M. P. (European Journal of Human Movement, 2017)
The aim of the study was to analyze the relationship between decision-making and performance in three game actions (reception, setting, attack), in male volleyball, U-19 category. The systematic observation was used to analyze 4014 game actions (1348 receptions, 1360 sets, 1306 attacks), corresponding to the 21 teams participating in the male U-19 Spanish Championship, held in 2012. Decision-making was associated to performance, in the actions of reception (.461**), setting (.750**), and attack (.276**). This results highlight the relevance of decisional skills in game actions` performance, that contribute to team final performance. Therefore, it would be appropriate to include decisional task in the process of training youth players, in order to improve their decisional skills, in these game actions.